The investigation of the influence of formation conditions on the structure of Ti-40Nb alloy; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Kovalevskaya Zh. G. Zhanna Gennadievna; Sharkeev Yu. P. Yury Petrovich; Khimich M. Margarita; Parilov E. Evgeny; Glukhov I. Ivan; Komarova E. Ekaterina (Materials structure and properties under modification, 2016)
Title screen